2017
DOI: 10.1158/0008-5472.can-16-1508
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MALAT1 Promotes Hepatocellular Carcinoma Development by SRSF1 Upregulation and mTOR Activation

Abstract: Several long noncoding RNAs (lncRNA) are abrogated in cancer but their precise contributions to oncogenesis are still emerging. Here we report that the lncRNA MALAT1 is upregulated in hepatocellular carcinoma (HCC) and acts as a proto-oncogene through Wnt pathway activation and induction of the oncogenic splicing factor SRSF1. Induction of SRSF1 by MALAT1 modulates SRSF1 splicing targets, enhancing the production of anti-apoptotic splicing isoforms and activating the mTOR pathway by modulating the alternative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
219
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(243 citation statements)
references
References 55 publications
18
219
0
Order By: Relevance
“…Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20]. MALAT1 was also found to promote colon cancer cell proliferation, invasion and metastasis in vitro and in vivo by increasing AKAP-9 expression [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20]. MALAT1 was also found to promote colon cancer cell proliferation, invasion and metastasis in vitro and in vivo by increasing AKAP-9 expression [28].…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 is localized to nuclear speckles, and regulates messenger RNA splicing by interaction with SR proteins and splicing factors [1416]. MALAT1 expression is upregulated in several solid tumors, including the breast, pancreas, lung, colon, prostate and liver [11], and is suspected to be involved in tumorigenesis or disease progression [1720]. In the present study, we analyzed MALAT1 expression in breast cancer and investigated its associations with clinical and pathological features and patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al32 reported that MYC stimulates the transcription of DANCR, and inhibition of DANCR impairs cell proliferation which could be partially rescued by p21 silencing in human ovarian cancer. In addition, lncRNA MALAT1 is upregulated in hepatocellular carcinoma and exerts oncogenic function through activating Wnt pathway by induction of splicing factor SRSF1 33. Besides, antisense lncRNA EZR‐AS1 promotes the mobility and invasiveness of ESCC cells through enhancing SMYD3‐dependent H3K4 methylation and transcription of the EZR gene 34.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (27) revealed that SNHG5/miR-32 axis regulated cell proliferation and migration of gastric cancer by targeting KLF4. Malakar et al (28) demonstrated that long noncoding RNA MALAT1 promoted hepatocellular carcinoma development by upregulating SRSF1 and activating mTOR. As for CRC, plenty well-studied lncRNAs have been reported to be dysregulated in CRC tissues and participate in CRC progression via multiple mechanisms (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%